2014
DOI: 10.2337/diaspect.27.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Update on Safety Issues Related to Antihyperglycemic Therapy

Abstract: The American Diabetes Association emphasizes the importance of individualized patient care in the management of diabetes. One of the important considerations in choosing an antihyperglycemic agent is its sideeffect and safety profile. This article reviews the common and clinically significant side effects of each class of agents, including ways to prevent and overcome their occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 80 publications
0
21
0
1
Order By: Relevance
“…Metformin, a drug that lowers oral blood glucose, is one of the most widely prescribed medications for type 2 diabetes (T2D) patients . However, about 30% of metformin‐treated patients report adverse gastrointestinal effects, including abdominal pain and diarrhoea which may be linked to metformin‐induced dysbiosis …”
Section: Resultsmentioning
confidence: 99%
“…Metformin, a drug that lowers oral blood glucose, is one of the most widely prescribed medications for type 2 diabetes (T2D) patients . However, about 30% of metformin‐treated patients report adverse gastrointestinal effects, including abdominal pain and diarrhoea which may be linked to metformin‐induced dysbiosis …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to control not only blood glucose levels but also blood lipid levels. It has been shown that current treatment for diabetes with synthetic hypoglycemic agents can cause adverse effects including hypoglycemia, gastrointestinal disturbances, renal toxicity and hepatotoxicity [6]. Hence, search of plant formulations with minimum toxicity remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, combined effects of SUs and TZDs can delay progression of T2D, the need of exogenous insulin therapy, reduce the risk of CVD as well as shows sustained glycemic control (Hanefeld, 2007). Although having much of the benefits in DM, hepatic metabolism of SUs, possibility of initiation of cancer by TZDs as well as longer duration of therapy as oral hypoglycemic drugs, they might produce detrimental effects on genetic material and DNA termed as genotoxicity (Agius, 2014;Carpio, 2014). Glimepiride (GMP) is the newest drug from SUs category having possible insulin sensitizing effect and longer duration of effect however, pioglitazone (PIO) is well tolerated in patients with renal failure and not associated with hypoglycemia (Craig, 2011;Matsuki, 2007;Richardson, 1976).…”
Section: Introductionmentioning
confidence: 99%